Movement Biomechanics and Motor Control - Frigo, Carlo Albino; Frigo, Carlo Albino (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This collection of original papers provides an overview of the state of the art of research in the area of human motor control, with an approach that has movement biomechanics as a common base. The reader can find interesting information in this book and a stimulus for new studies and investigations.
English
Keywords: Medicine